Społeczne i ekonomiczne przesłanki sycylijskiego separatyzmu od zjednoczenia Włoch do połowy XX wieku. Mafia a kwestia niepodległości Sycylii ​ - Janek, Jolanta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2018)
The article presents broad historical context, including socio-economic factors, of the rise and periodic resurgence of the movement for Sicilian independence following the unification of Italy in the 1860s. Furthermore, the involvement of Cosa Nostra in the movement for Sicilian independence in the period beginning with the Allied invasion of Sicily during the Second World War is analysed.